PENGARUH MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN TEMATIK TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V - Faiza, Yulinur; Kartono, Kartono; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the effect of the use of Problem Based Learning Models on Thematic Learning Against Student Learning Outcomes Class V of South Pontianak 14 Primary School. The experimental method design of this research is Quasi Experimental Design with Nonequivalent Control Group Design. The research sample is the VA class being the experimental class and the VB class being the control class selected by purposive sampling technique. Data collection tools used in the form of multiple choice totaling 45 questions. Based on data analysis, the average post test grade test result is 79.25 and the average post test grade test result is 71.07. T test results obtained tcount 2.624 and t table ? = 5% (with dk = 24 + 23 - 2 = 45) of 2.016, which means tcount (2.624)> t table (2.016), then Ha is accepted. It can be concluded that there is an influence of the use of Problem Based Learning models on Thematic Learning on the learning outcomes of Students in grade V SD Negeri 14 South Pontianak. From the calculation of the effect size of 0.69 (medium criteria). This means that the use of Problem Based Learning models has a good effect on Thematic Learning Outcomes of Students in Grade V of South Pontianak 14 Primary School. Keywords: Influence, Learning Outcomes , Problem Based Learning, Thematic Learnin